English grammar all-in-one for dummies - Woods, Geraldine (--For dummies., 2023)
English Grammar All-in-One For Dummies is packed with everything you need to know to communicate with confidence--in your writing, on standardized tests, at work, on social media, and everywhere else. Strong verbal and written skills can help you get where you want to be, and this easy-to-understand Dummies guide will help you understand the English grammar principles you need to know so you can improve your understanding of basic grammar and punctuation rules, easily identify parts of speech, and communicate more effectively.